2006
DOI: 10.1071/he06226
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, not smoking: how important is where you live?

Abstract: The level of disadvantage of the residential neighbourhood has a unique, statistically significant influence, but not to the same degree as previously published Australian research. The effect is consistent across individual characteristics such as age and level of education for men. The effect is small and less consistent for women. Indeed, area of residence seems less important for women as a whole, suggesting differential influences according to gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…This finding is consistent with previous research which finds that the likelihood of quitting is significantly lower among residents of disadvantaged neighbourhoods [38][39][40]. A larger body of work has investigated the relationship between neighbourhood disadvantage and smoking, and like this present study, these find that residents of disadvantaged neighbourhoods are significantly more likely to smoke after adjustment for individual-level socioeconomic factors [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Additionally, we observed widening inequalities in smoking as indicated by greater betweenneighbourhood variation in smoking rates in 2009 compared with 2007, and increased relative inequalities in smoking between residents of the least and most disadvantaged neighbourhoods.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with previous research which finds that the likelihood of quitting is significantly lower among residents of disadvantaged neighbourhoods [38][39][40]. A larger body of work has investigated the relationship between neighbourhood disadvantage and smoking, and like this present study, these find that residents of disadvantaged neighbourhoods are significantly more likely to smoke after adjustment for individual-level socioeconomic factors [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Additionally, we observed widening inequalities in smoking as indicated by greater betweenneighbourhood variation in smoking rates in 2009 compared with 2007, and increased relative inequalities in smoking between residents of the least and most disadvantaged neighbourhoods.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous research which finds that the likelihood of quitting is significantly lower among residents of disadvantaged neighbourhoods [38–40]. A larger body of work has investigated the relationship between neighbourhood disadvantage and smoking, and like this present study, these find that residents of disadvantaged neighbourhoods are significantly more likely to smoke after adjustment for individual‐level socioeconomic factors [7–20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Smoking behaviors are strongly related to sociodemographics factors of individual smokers and their households such as education, income, race, sex, marital status, and age. Neighborhood characteristics such as poverty, access to cigarettes, exposure to cigarette advertisements as well as tobacco control programs also affect smoking behavior(Migliorini and Siahpush, 2006; Reid et al, 2010; Siahpush et al, 2010; Siahpush et al, 2007; Siahpush et al, 2009; Wakefield et al, 2008)(Barbeau et al, 2004)(Diez Roux et al, 2003; Duncan et al, 1999; Kandula et al, 2009; Reijneveld, 1998; Tseng et al, 2001). (Reijneveld, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Research that examines the social context of smoking suggests that smoking should not be viewed exclusively as an individual behavior, but should be recognized as a collective social practice (55). For instance, studies suggest that smokers find it difficult to quit when they are embedded in an environment where anti-smoking norms are weak and smoking is socially acceptable (56). Studies that have investigated the influence of social norms on smoking behaviors have found that smoking-related norms are predictors of smoking behavior across a range of countries (57)(58)(59)(60).…”
Section: Smoking-related Social Normsmentioning
confidence: 99%